2022
DOI: 10.4103/aer.aer_134_22
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Severity of Postoperative Complications in Patients Undergoing Surgery Following COVID-19 Infection at a Tertiary Care Center in South India

Abstract: Background: The occurrence of postoperative pulmonary complications (PPCs) and other sequelae of COVID-19 infections like thromboembolic events in patients coming for surgery following COVID-19 infection in the Indian population had not been adequately studied. Aim of the Study: We evaluated the incidence of PPCs, acute kidney injury, and thromboembolic complications such as pulmonary embolism, deep-vein thrombosis, myocardial infarction, stroke, and 30-day mortality ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It has been reported that the complication rate may be low because the study was performed in a period when the Omicron variant was common. [ 7 ] Delta variant was common in our country during the study period. As it is known, disease severity was higher in the Delta variant compared to Omicron.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It has been reported that the complication rate may be low because the study was performed in a period when the Omicron variant was common. [ 7 ] Delta variant was common in our country during the study period. As it is known, disease severity was higher in the Delta variant compared to Omicron.…”
Section: Discussionmentioning
confidence: 82%
“…As it is known, COVID-19 affects all body systems, but mainly the respiratory system. [ 7 ] According to the subgroup analysis, we found that the incidence of perioperative airway complications and the need for postoperative oxygen support also decreased independently, as the time from COVID-19 to the operation was prolonged.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation